THE CONCEPT OF MASLAHAH ACCORDING TO IMAM AL-GHAZALI - Tarmizi Tarmizi (IAIN Bone, 2020)
Maslahah is the study of the aims and the objectives of Islamic Law. Maslahah is often used by Ulema as a method in resting the law to answer the legal problems that arise. Al-Ghazali mentioned various types of Maslahah viewed from whether it is acknowledged or not by the Shari’ah, which is divided into three types: Maslahah that is acknowledged by the Shari’ah, Maslahah that is rejected by the Shari’ah, and Maslahah that is neither acknowledged nor rejected by the Shari’ah. Studying the term Maslahah that is associated with the development of modern society is of utmost importance. Maslahah can act as the necessary foundation for the realization of all human interests, both general and specific. So the spirit of Islam, shalih li kullizamaninwamakanin can be realized.